RETHINKING RELIGIOUS LANGUAGE IN THE AGE OF SCIENCE - Tharakan, Koshy (Journal of Dharma, 2008)
Relation of science and religion has been at the centre of many discourses in the past as well as in the recent times. Some of these were meant to refute religious claims in the light of scientific truths about the world, while others took the pain of explaining the essential compatibility between the two. The former subjects religion to the scrutiny of science while the latter reads science in religion or religion in science.1 Both these attempts are ill-conceived as they conflate the logic of one with the other. Ian G. Barbour, who has pioneered the philosophical debate between science and religion, provides four typologies to relate the two domains of science and religion, namely, conflict, independence, dialogue, and integration.2 Nevertheless, his position is one that treats the two as distinct disciplines and yet sharing a common ground rather than two separate and conflicting discourses. In what follows, we attempt to understand the nature of the interaction of these two, science and religion, from a phenomenological perspective. In order to do that, we have to look into the ‘life-world’ (Lebenswelt) that engenders science and houses religious experiences.